A landscape analysis of psychedelic retreat organizations advertising online - Logan Neitzke-Spruill; Caroline S. Beit; Jill Oliver Robinson; Nikita Singh; Srijith Kambala; Rishi Ramesh; Amy L. McGuire (PLoS ONE, 2025)
Research into psychedelics’ clinical potential has corresponded to a growth in public interest and adult use. One common pathway to accessing psychedelics is through psychedelic retreats. While individual retreats have been characterized in the anthropological literature, no systematic evaluation of the psychedelic retreat industry exists. Assessing the characteristics of the psychedelic retreat industry is critical to understanding the associated ethical, legal, and social implications and ensuring consumer safety. To this end, we conducted a landscape analysis of online, publicly available information to capture and characterize a broad range of organizations offering psychedelic retreats and marketing to English-speaking consumers. From July 2023 to December 2023, we identified 298 psychedelic retreat organizations. Some identified as religious organizations, but the majority focused on general wellness. Organizations offered various psychedelic substances with ayahuasca being the most common, followed by psilocybin and San Pedro. Organizations held retreats across the globe at various price points. In total, there were 440 distinct physical locations where retreat experiences were held; 130 were inside the United States (U.S.) and 310 were outside the U.S. Further research into the practices of psychedelic retreat organizations is recommended to help reduce harm and support consumer education.